Efforts to Improve the Earthquake Resistance of the Kagawa Prefectural Government Office East Building - Hamada, Keizo (Docomomo Journal, 2015)
The Kagawa Prefectural Government Office East Building, designed by Kenzo Tange, was completed in 1958, and in addition to acting as an important disaster prevention base facility, it possesses a cultural value through its many spaces open to the public and its expression of traditional Japanese architectural ideas in concrete. It is part of the current government offices, and while the concrete itself is expected to be viable for over 50 years, it will require substantial improvements in order to meet the most recent earthquake resistance standards. As such, Kagawa Prefecture, through advice from specialists and discussion in the Prefectural Assembly, has considered the possible earthquake resistance improvements that could be made, including reconstruction, seismic isolation retrofitting, and seismic strengthening. It was concluded that in consideration of earthquake resistance, its office functions, costs involved, and the cultural value of the building, it would be appropriate to preserve the building and improve its earthquake resistance through base isolation construction methods, and efforts are being made to gain the support and understanding of the people of the prefecture and pursue this policy going forward.